Analysis of the Community Satisfaction Survey of the Faculty of Vocational Studies - Pratiwi, Amelia Ika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
Analysis of the Vocational Faculty Community Satisfaction Survey (SKM). This research was conducted as a medium for decision making for FV in developing a stakeholder satisfaction index program in the FV environment. This research was conducted in units at the Faculty of Vocational Studies, Brawijaya University. The Community Satisfaction Survey (SKM) for the Even 2022-2023 and Odd 2023-2024 periods was carried out in all work units of the Faculty of Vocational Studies starting from June-October 2023. Data collection techniques in this research were carried out by means of questionnaires and observations. The results of the research show that the implementation of the SKM for the first semester of 2023 has gone smoothly and according to the schedule that has been determined with the number of participating respondents having exceeded the minimum requirements determined by PERMENPAN No. 14 of 2017.